2015
DOI: 10.1177/1557988315585164
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in Health Care: Correlates of Health Care Discrimination Among Black Males

Abstract: Using data from the Indiana Black Men's Health Study (N = 455), a community-based sample of adult Black men, the primary aim of this study was to explore factors of health care discrimination, and to examine if such reports differed by age and the frequency of race thoughts. Approximately one in four men reported experiencing discrimination in the health care setting. Results from the multivariable logistic regression models suggested that frequent race thoughts (odds ratio [OR]: 1.89, p < .05), not having hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Furthermore, biological differences in cancer subtypes may be relevant to some cancer sites: Black AYAs are more likely to be diagnosed with breast cancer molecular subtypes associated with a shorter prognosis [48], and it has been reported that inclusion of molecular subtype and insurance type in survival models diminishes the association of Black race/ethnicity with greater risk of death [9]. While studies of the effects of racial/ethnic discrimination have not been conducted specifically among AYAs, it has been observed that discrimination may impact care utilization (independent of insurance status) [4951], and that chronic stress due to discrimination impacts health outcomes [5254]. In addition, greater racial/ethnic disparities for cancers more amenable to prevention and treatment suggest that differences in access to social and economic resources (social capital) likely contribute to residual racial/ethnic disparities in cancer survival [55].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, biological differences in cancer subtypes may be relevant to some cancer sites: Black AYAs are more likely to be diagnosed with breast cancer molecular subtypes associated with a shorter prognosis [48], and it has been reported that inclusion of molecular subtype and insurance type in survival models diminishes the association of Black race/ethnicity with greater risk of death [9]. While studies of the effects of racial/ethnic discrimination have not been conducted specifically among AYAs, it has been observed that discrimination may impact care utilization (independent of insurance status) [4951], and that chronic stress due to discrimination impacts health outcomes [5254]. In addition, greater racial/ethnic disparities for cancers more amenable to prevention and treatment suggest that differences in access to social and economic resources (social capital) likely contribute to residual racial/ethnic disparities in cancer survival [55].…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of prior research has yielded important insights into the dangerous implications of experiencing racial discrimination for health outcomes among underrepresented minorities, and Blacks in particular [ 2 , 13 , 57 ]. When Black patients perceive that they are not being listened to, respected, and or given enough time to ask questions or interact with clinicians during medical visits, and that this treatment may be due to their race, studies show that they are more likely to mistrust providers, delay preventive care [ 16 , 17 ], have poor glycemic control [ 58 ], and experience increased depressive symptomology [ 59 ]. Research clearly demonstrates that Black patients often attribute poor and ineffective clinical communication to discrimination; particularly when they perceive their health symptoms or perspectives are being overlooked or discredited during medical visits [ 40 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following two items were used, “within the past 12 months at work, do you feel you were treated worse than, the same as, or better than people of other races?” and “within the past 12 months, when seeking health care, do you feel you were treated worse than, the same as, or better than people of other races?” The responses were: 1) worse than other races, 2) the same as other races, 3) better than other races, 4) worse than some races better than other races, and 5) only encountered people of the same race. Following the work of previous studies (Crawford, Jones, & Richardson, 2010; Hausmann, Jeong, Bost, & Ibrahim, 2008; Parker, Hunte, & Ohmit, 2015), for both items, the response “worse than other races” was coded as experiencing healthcare discrimination, and “the same as, or better than people of other races” and “better than other races” were coded as not experiencing healthcare discrimination in the health care setting. The responses “worse than some races better than other races” and “only encountered people of the same race” were treated as missing because they did not indicate a strong sense of favorable or unfavorable treatment (Crawford et al, 2010; Hausmann et al, 2008; Parker et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Following the work of previous studies (Crawford, Jones, & Richardson, 2010; Hausmann, Jeong, Bost, & Ibrahim, 2008; Parker, Hunte, & Ohmit, 2015), for both items, the response “worse than other races” was coded as experiencing healthcare discrimination, and “the same as, or better than people of other races” and “better than other races” were coded as not experiencing healthcare discrimination in the health care setting. The responses “worse than some races better than other races” and “only encountered people of the same race” were treated as missing because they did not indicate a strong sense of favorable or unfavorable treatment (Crawford et al, 2010; Hausmann et al, 2008; Parker et al, 2015).…”
Section: Methodsmentioning
confidence: 99%